Development of non-data driven reservoir routing in the routing application for parallel computatIon of discharge (RAPID) model. (March 2023) - Tavakoly, Ahmad A.; David, Cédric H.; Gutenson, Joseph L.; Wahl, Mark W.; Follum, Mike
Abstract: Dams and reservoirs predictably alter the discharge of a river often confounding large-scale flow simulations. The Routing Application for Parallel computatIon of Discharge (RAPID) model has been widely used operationally. Until recently, RAPID could only represent reservoir outflow by directly specifying discharges from dams. Herein, we develop a non-data driven reservoir routing approach within RAPID. Results are comprehensively evaluated across the entire Mississippi River Basin (MRB). The reservoir routing resulted in considerable improvement in the Lower Mississippi and Arkansas-White-Red regions. Further, the accuracy of estimated reservoir releases also benefits when the inflow estimation improves. Simulation of the reservoir release with observed reservoir inflow resulted in highest Kling-Gupta efficiency (KGE) among all experiments. Inclusion of reservoir routing in RAPID will enhance the utility of this model in basins where dams exist and more importantly, improves streamflow predictions by providing better hydrological information for decision makers. Highlights: A reservoir approach was developed for large-scale river flow simulation. Continental scale streamflow simulation improves with the reservoir model. The impact of reservoirs on downstream flow depends on the proximity to the dam.